Telesne značilnosti plesalk in plesalcev hip hopa ter njihova povezanost z uspešnostjo na tekmovanjih - Pruš, Daša (Šport (Ljubljana), 2018)
The purpose of the study was to analyze physical characteristics of hip hop dancers and to determine their connection wiht performance in competitions. Hip hop dance is a conventional aesthetic sport, where body image is inseparable with the choreography and performance. The sample consisted of 60 dancers, from two Slovenian dance schools, who compete in the Dance Association of Slovenia (PZS) and the International Dance Association (IDO). Dancers all achieved enviable results both at the national and international competitions. The body composition data was obtained with TANITA scale (Tanita, Innerscan body composition monitor, model BC-545), body height was measured with anthropometer and basic data about dancers where obtained through anonymous survey. The results showed that more successful dancers have less subcutaneous fat and more muscle mass, bone mass, and a higher proportion of water in the body in comparison with less successful dancers. The reaserch findings can be used as a foundation for future work on exploring the influence of body atributes on dance performance among hip hop dancers and guidance for all choreographers and dancers.
Keywords: hip hop; ples; tekmovalna uspešnost; telesne značilnosti